2015
DOI: 10.14348/molcells.2015.0007
|View full text |Cite
|
Sign up to set email alerts
|

Cell Proliferation and Motility Are Inhibited by G1 Phase Arrest in 15-kDa Selenoprotein-Deficient Chang Liver Cells

Abstract: The 15-kDa selenoprotein (Sep15) is a selenoprotein residing in the lumen of the endoplasmic reticulum (ER) and implicated in quality control of protein folding. Herein, we established an inducible RNAi cell line that targets Sep15 mRNA in Chang liver cells. RNAi-induced Sep15 deficiency led to inhibition of cell proliferation, whereas cell growth was resumed after removal of the knockdown inducer. Sep15-deficient cells were arrested at the G1 phase by upregulating p21 and p27, and these cells were also charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
0
14
1
Order By: Relevance
“…The expression levels of Sep15 were investigated in various cancer models: downregulation of the protein was found in hepatocarcinomas and colorectal, gastric, and prostate cancers [53, 54, 60, 61]. On the other hand, decreased expression of Sep15 reduces proliferation and growth of liver and colon cancer cell lines, pointing to a role of Sep15 in tumour progression [60, 6264]. Single-nucleotide polymorphisms in the Sep15 gene have been studied in conjunction with differential levels of selenocysteine insertion [65] and susceptibility to lung and breast cancer [6668], highlighting the need for a stratified medicine approach in the development of Sep15 modulators as anticancer therapeutics.…”
Section: Methodsmentioning
confidence: 99%
“…The expression levels of Sep15 were investigated in various cancer models: downregulation of the protein was found in hepatocarcinomas and colorectal, gastric, and prostate cancers [53, 54, 60, 61]. On the other hand, decreased expression of Sep15 reduces proliferation and growth of liver and colon cancer cell lines, pointing to a role of Sep15 in tumour progression [60, 6264]. Single-nucleotide polymorphisms in the Sep15 gene have been studied in conjunction with differential levels of selenocysteine insertion [65] and susceptibility to lung and breast cancer [6668], highlighting the need for a stratified medicine approach in the development of Sep15 modulators as anticancer therapeutics.…”
Section: Methodsmentioning
confidence: 99%
“…To construct a knockdown-resistant (rescue) SPS1 expression vector, three silent point mutations were introduced into the shRNA target sequence by two-step PCR [22]. In the first step, two DNA fragments (the 5′-half and the 3′-half) were amplified from the mouse F9 cell cDNA using two sets of primers: the SPS1 KI-F1 and the SPS1 KI-R1 for the 5′-half, and the SPS1 KI-F2 and the SPS1 KI-R2 for the 3′-half (Table S1; altered bases are under-lined).…”
Section: Methodsmentioning
confidence: 99%
“…SELENOH is a selenium-sensitive SePs with a disturbed expression under suboptimal selenium concentrations. Unlike GPx2, TXNRD1 and SELENOF, knockdown of SELENOH improves cell proliferation in vitro and promotes tumor growth in vivo, indicating that SELENOH may suppress tumor progression (79)(80)(81)(82). SELENOH affect cell cycle through inhibition of G1/S transition by modulating p21 and CCNE1 expression (83,84).…”
Section: Resultsmentioning
confidence: 99%
“…The 15-kDa selenoprotein (Sep15) can also contribute to cancer progression (85)(86)(87)(88)(89). A study reported that Sep15-deficient Chang liver cells are arrested at the G1 phase by upregulation of p21 and p27 (82). Both p21 and p27 inhibit cell cycle progression by interacting with cyclins and CDKs (90).…”
Section: Resultsmentioning
confidence: 99%